Antioxidant capacity and phenolic content of a beverage based on jamaica flower (Jamaica sabdariffa) enriched with mulberry (Vaccinium floribundum) and blackberry (Rubus glaucus) - Núñez, Pablo (2024)
The objective of this research was to evaluate the antioxidant capacity and phenolic content of a Jamaica flower-based drink enriched with mulberry and blackberry, for which it was proposed to study two factors: the concentration of Jamaica flower for the infusion and the percentage used of blackberry and mulberry. Treatment 9 made with 5% Jamaica flower and 95% water; 75% mulberry and 25% blackberry and treatment 8 made with 5% Jamaica flower and 95% water; 59% mulberry and 50% blackberry did not differ statistically in the sensory tests, obtaining the highest acceptance by the panel. The content of phenols analysis showed a result of 89.5 mg/L; while the antioxidant capacity presented 1732 mg EAG/L. Based on the results obtained in the microbiological analysis, the absence of pathogens (yeast, mold and mesophilic aerobes) was evidenced at 0, 15 and 30 days of storage, which implies that the drink will have a useful life of at least 30 days.